2020
DOI: 10.1037/hea0000849
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of physical activity behavior change in an incentive-based intervention: Mediation analysis.

Abstract: Objective: The Physical Activity Loyalty (PAL) scheme was a cluster randomized controlled trial of a 6-month complex intervention targeting workplace physical activity. Financial incentives were incorporated in an evidence-based behavior change programme, including self-regulation techniques. This article examines shortterm ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Indeed, findings from a meta-analysis of SDT-based interventions in health behavior change provided significant but small effect of SDT variables on health behaviors (Sheeran et al, 2020). For instance, Murray and colleagues (Murray et al, 2020) found effectiveness of a behavioral intervention on targeted mediators but these changes were not translated in increases in device-measured PA behavior (however in this case using a Yamax Digitwalker CW-701 pedometer). Also, Sebire et al (2011) found limited predictive capacity of a simpler SDT based mediation model on device measured MVPA minutes (R 2 = 0.07).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, findings from a meta-analysis of SDT-based interventions in health behavior change provided significant but small effect of SDT variables on health behaviors (Sheeran et al, 2020). For instance, Murray and colleagues (Murray et al, 2020) found effectiveness of a behavioral intervention on targeted mediators but these changes were not translated in increases in device-measured PA behavior (however in this case using a Yamax Digitwalker CW-701 pedometer). Also, Sebire et al (2011) found limited predictive capacity of a simpler SDT based mediation model on device measured MVPA minutes (R 2 = 0.07).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, digitally enabled psycho-social assessments are predicted to be innovative in the field of human behavior change (Arigo et al, 2019;Wadden et al, 2020), and they may overcome some limitations of the classical timepoint specific intervention studies. Digital technologies enable collection of information from participants more often and are not strictly fixed to specific time points of assessment (continuously for six months) (Murray et al, 2020;Scholz, 2019;Sniehotta, Presseau, & Araújo-Soares, 2014). Furthermore, digitally enabled assessments may reduce participant burden with briefer and shorter scales.…”
Section: Discussionmentioning
confidence: 99%
“…In these analyses, each variable was coded with a change score, such that positive changes indicated high scores on assessed variables. Criteria for mediation included significant intervention effects on the mediator, significant associations between the mediator and the dependent variable (i.e., RT), and a significant effect of the intervention on RT through the mediator (25). Effects were estimated using structural equation modeling in which models tested the pathways between changes in the constructs and treatment (a path) and changes in the constructs and changes in behavior (b path).…”
Section: Methodsmentioning
confidence: 99%
“…Identification is hence distinguished from integrated regulation, the most autonomous form of extrinsic motivation, which manifests in fully self-congruent and reflectively valued behaviours. Crucially, studies that examine identified and integrated regulations alongside intrinsic motivation [79,352,379,509] suggest that both forms of autonomous motivation predict beneficial psychosocial outcomes [e.g., lower anxiety; 509] and behaviours [e.g., engagement ; 352]. Initially, SDT research measured internalisation by constructing a Relative Autonomy Index [216], which "approximates an individual's position along the underlying continuum of self-determination" [254, p. 536] using weighted self-report data.…”
Section: Organismic Integration Theorymentioning
confidence: 99%